2017
DOI: 10.1007/s00392-016-1075-9
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of acute myocardial infarction in patients with mild elevations of cardiac troponin

Abstract: About 6-22% of patients presenting with suggestive AMI to the ED have mild hs-cTnT/I elevations at presentation. In contrast to copeptin, the addition of 1h-hs-cTn changes substantially improves the early diagnosis of AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
4
21
0
2
Order By: Relevance
“…Advantageous Predictors of Acute Coronary Syndrome Evaluation (APACE) is an ongoing prospective international multicenter study designed to advance the early diagnosis of AMI (ClinicalTrials.gov registry, number NCT00470587) (Reichlin et al., , , ; Boeddinghaus et al., , ). Unselected patients presenting to the ED with symptoms suggestive of AMI (such as acute chest discomfort and angina pectoris) with an onset or peak within the last 12 hr and an age >18 were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Advantageous Predictors of Acute Coronary Syndrome Evaluation (APACE) is an ongoing prospective international multicenter study designed to advance the early diagnosis of AMI (ClinicalTrials.gov registry, number NCT00470587) (Reichlin et al., , , ; Boeddinghaus et al., , ). Unselected patients presenting to the ED with symptoms suggestive of AMI (such as acute chest discomfort and angina pectoris) with an onset or peak within the last 12 hr and an age >18 were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…For rapid rule-out in AMI patients with hs-cTn, two alternative approaches using the 0 h/1 h algorithm or 0 h/3 h algorithm have been adequately validated and may be considered [20]. It has been confirmed that the addition of the 1h-hs-cTn measurement significantly promotes the diagnostic accuracy in the patients with mild cTn elevation [27]. e ESC recommended that the rule-in using the 0 h/3 h algorithm has a high positive predictive value, while the sensitivity remains too low for clinical use [28].…”
Section: Cardiac Troponinmentioning
confidence: 99%
“…Subsequently, we analyzed different subgroups: patients hospitalized in the cardiology department (Subgroup 1), patients hospitalized in other departments (Subgroup 2), and lastly, to investigate the findings in a cohort of patients with high a priori probability for the diagnosis of acute myocardial infarction (Subgroup 3), we applied clinically relevant laboratory criteria to all inpatients of the cardiology department in a separate analysis: with high-sensitivity troponin testing based on the ESC hs-TnT 0/1h algorithm [7,8,24,25] and regarding patients with conventional troponin testing with markedly elevated cTnI values (i.e., 5 times the normal upper limit) or a 50% dynamic change between two serial measurements.…”
Section: Study Populationmentioning
confidence: 99%